Breeding ecology of the Tree Sparrow in Western Poland - Ciebiera, Olaf; Gajda, Krzysztof; Stamm, Arkadiusz; Szczepaniak, Katarzyna; Cieniuch, Paweł; Zajdel, Monika; Czechowski, Paweł (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
From 2013 to 2015, the Lubuskie Landscape Parks Complex implemented a project for the active protection of the Tree Sparrow ("Passer montanus"). Nest boxes were installed in all Lubuskie Landscape Parks, and the rate of occupancy as well as the breeding process was monitored. The aim of the study was to describe selected parameters of biology and reproductive ecology of the Tree Sparrow population breeding in the nest boxes.
Keywords: Tree Sparrow Passer montanus; Landscape Parks; Lubuskie Province; breeding ecology